Structure and chemical characteristics of tin oxide films prepared by reactive-ion-assisted deposition as a function of oxygen ion beam energy - Song, SK; Kim, D; Kim, S; KOH, SEOK KEUN; JUNG, HYUNG JIN; Lee, JY; Baik, HK (Materials Research Society, 2000)
Tin oxide films were deposited on amorphous SiO2/Si and Si (100) substrates by ion-assisted deposition (IAD) at various ion beam potentials (V-I) at room temperature and a working pressure of 8 x 10(-5) ton. The structural and chemical properties of the as-grown tin oxide films were investigated to determine the effects of the oxygen ion/atom arrival ratio (R-i). X-ray diffraction patterns indicated that the as-grown films with different average energy per atom (E-ave) showed different growth directions. The as-grown films with oxygen/Sn ratio (N-O/N-Sn) of 2.03 and 2.02 had preferred orientation of (101) and (002), respectively. In addition, the as-grown film with low R-i was amorphous. Comparison of the observed d spacings with those for standard SnO2 samples, indicated that the crystalline as-grown films had compressive and tensile stress depending on E-ave. In transmission electron microscopy analysis, a buffer layer of amorphous tin oxide was observed at the interface between the substrate and the film, and the crystalline grains were grown on this buffer layer. The crystalline grains were arranged in large spherical clusters, and this shape directly affected surface roughness. Rutherford backscattering spectroscopy spectra showed that the tin oxide thin films were inhomogeneous. The density of films decreased and the porosity and oxygen trapped in the films increased with increasing R-i. The densest film had about 6% porosity.